2020
DOI: 10.2355/isijinternational.isijint-2019-712
|View full text |Cite
|
Sign up to set email alerts
|

Phase Composition and Properties Distribution of Residual Iron in a Dissected Blast Furnace Hearth

Abstract: Dissection research is the most meaningful way to understand the internal conditions of blast furnace. Because it can obtain samples from hearth after a blast furnace was shut down. In this paper, a 2 200 m 3 commercial blast furnace was shut down with residual iron remained inside. And then core drilling method was used to obtain a horizontal sample of residual iron, which was located 1 610 mm below the centerline of taphole and had a length of 1 840 mm. A variety of techniques, such as scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Zhang et al 21) analyzed the phase composition of the residual iron in the hearth and found that the residual iron near the carbon brick side contains phases such as Ti 3 N 2 , KAlSi 2 O 6 , and Al 2 O 3 . These studies are important to understand the state of trace elements in the hearth.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 21) analyzed the phase composition of the residual iron in the hearth and found that the residual iron near the carbon brick side contains phases such as Ti 3 N 2 , KAlSi 2 O 6 , and Al 2 O 3 . These studies are important to understand the state of trace elements in the hearth.…”
Section: Introductionmentioning
confidence: 99%